2019
DOI: 10.1111/aswp.12190
|View full text |Cite
|
Sign up to set email alerts
|

Social investment effects of public education, health care, and welfare service expenditures on economic growth

Abstract: | INTRODUC TI ONThe purpose of this study is twofold: to review theoretical literature on the social investment mechanism of social services and to offer empirical evidences about social investment effects especially in key social services areas including health care, education, and welfare services with a focus on its impact on economic growth.The "productivity of welfare" has been a long-standing issue in the academic arena of the welfare state theories. With almost no exception, especially when it comes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The authors analyze the impact of these investments on enhancing human capital formation, promoting labour market participation, and creating new jobs. The results confirmed that public spending on education, health care, and social services had positive medium-and long-term effects on economic performance (Kim & Ahn, 2020). Regarding our problem, we examine the ex-post impact of education spending stemming from educational attainment.…”
Section: Discussionmentioning
confidence: 56%
“…The authors analyze the impact of these investments on enhancing human capital formation, promoting labour market participation, and creating new jobs. The results confirmed that public spending on education, health care, and social services had positive medium-and long-term effects on economic performance (Kim & Ahn, 2020). Regarding our problem, we examine the ex-post impact of education spending stemming from educational attainment.…”
Section: Discussionmentioning
confidence: 56%
“…Using instrumental variable estimations or the two-system GMM estimator, Table 1 shows how different types of government spending affect TFPI. The results show that spending money on health impacts significantly TFP, because there is a high risk of pandemics in these countries, their economies are not very strong, and they have large populations and low standards of living ( Bhorat et al., 2021 ; Kim and Ahn, 2020 ). Deaton (2013) says that health, which is a reflection of human ability, is the basis for human progress and development.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…According to another approach, government social expenditures are understood in the context of intentions to bring the country closer to a certain ethical ideal, in which social justice will be ensured, and the idea of a "welfare state for liberty" is embodied (Béland et al, 2021, p. 23). In the mentioned work (Béland et al, 2021), the modern discourse of such views is considered quite thoroughly, as well as in other works containing a theoretical justification of the foundations of the welfare state, directions of its regulatory influence (Nelson et al, 2020;Wilson & Wilson, 2021), as well as empirical evidence of the effectiveness of relevant government programs (Kim & Ahn, 2020;Lessa Kerstenetzky & Pereira Guedes, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%